Dendritic cells induce Tc1 cell differentiation via the CD40/CD40L pathway in mice after exposure to cigarette smoke - Kuang, Liang-Jian; Deng, Ting-Ting; Wang, Qin; Qiu, Shi-Lin; Liang, Yi; He, Zhi-Yi; Zhang, Jian-Quan; Bai, Jing; Li, Mei-Hua; Deng, Jing-Min; Liu, Guang-Nan; Liu, Ji-Feng; et al. (American journal of physiology. Lung cellular and molecular physiology, 2016)
Dendritic cells and CD8 + T cells participate in the pathology of chronic obstructive pulmonary disease, including emphysema, but little is known of the involvement of the CD40/CD40L pathway. We investigated the role of the CD40/CD40L pathway in Tc1 cell differentiation induced by dendritic cells in a mouse model of emphysema, and in vitro. C57BL/6J wild-type and CD40 −/− mice were exposed to cigarette smoke (CS) or not (control), for 24 wk. In vitro experiments involved wild-type and CD40 −/− dendritic cells treated with CS extract (CSE) or not. Compared with the control groups, the CS mice (both wild type and CD40 −/− ) had a greater percentage of lung dendritic cells and higher levels of major histocompatability complex (MHC) class I molecules and costimulatory molecules CD40 and CD80. Relative to the CS CD40 −/− mice, the CS wild type showed greater signs of lung damage and Tc1 cell differentiation. In vitro, the CSE-treated wild-type cells evidenced more cytokine release (IL-12/p70) and Tc1 cell differentiation than did the CSE-treated CD40 −/− cells. Exposure to cigarette smoke increases the percentage of lung dendritic cells and promotes Tc1 cell differentiation via the CD40/CD40L pathway. Blocking the CD40/CD40L pathway may suppress development of emphysema in mice exposed to cigarette smoke.